FORMULATION NANOEMULSION OF ETHANOLIC EXTRACT SAFFLOWER (Carthamus tinctorius L.) AND IN VITRO ACTIVITY TEST - Aspadiah, Vica
The Safflower extract (Carthamus tinctorius L.) has phytochemical contents which were flavonoids, alkaloids, tannins, quinones and terpenoids, it had potential in several pharmacological activities. The activity of compound can be increased using nanoemulsion preparations. The aims of this study were to produce a stable nanoemulsion containing ethanolic safflower extract and to determine anticoagulant activity, antioxidants, inhibition of xanthine oxidase and inhibition of acetylcholinesterase. Safflowers were extracted using 96% ethanol by maceration method. The formation of nanoemulsion was carried out using combination of homogenization and ultrasonic methods. Extract obtained was 60.303 g. The optimum formula was obtained using Tween 80 (2.5%), Span 80 (2.5%), Cremophor RH 40 (7.5%) and PEG400 (2.5%) with oleic acid as the oil phase. The results of the stability testing of nanoemulsion were physically and chemically stable at 25°C and 40°C. In vitro activity test results showed that the ethanolic extract of safflower and nanoemulsions with concentrations 10 mg/ml could prolong the coagulation time of activated Prothrombine Time (aPTT) up to 60 ± 2.82 and 96.3 ± 4.38, prolonging the time of Thrombine Time (TT) up to 31.5 ± 2.26 and 43.7 ± 0.21 seconds. However, it slightly prolonged the coagulation time of Prothrombine Time (PT). The IC50 value of antioxidant extract and nanoemulsion were 146.019 ± 2.94 µg / ml and 107.698 ± 3.89 µg / ml, IC50 inhibition of xanthine oxidase enzyme for extract and nanoemulsion were 89.3 ± 0.85 µg / ml and 60.071 ± 4.28 µg / ml, but had no inhibition activity against acetylcholinesterase enzyme. The nanoemulsion can increase the anticoagulant, antioxidants and inhibition of xanthine oxidase enzyme activity.